Economic Activities in Riverbanks Community Settlement in Benua Anyar Village - Muhammad Adhitya Hidayat Putra; Herry Porda Nugroho Putro; Syaharuddin Syaharuddin; Muhammad Rezky Noor Handy; M. Ridha Ilhami; Nona Ayuriszki; Muhammad Risalan Uzhma (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
The riverside area is an area where there are also many residential areas around it. Usually, a group living on the river's banks is called a riverbank community. This research process used a qualitative approach to the type of case study research. The research was conducted in the Banua Anyar sub-district, with the research subjects being the Banua Anyar sub-district community. Continental Anyar Village is a culinary tourism village in terms of carrying out economic activities. With the development of culinary tourism, it is assumed that it can bring changes to the socio-economic sector, especially the small and informal economic sectors. The existence of small traders, souvenir traders, typical restaurants, and so on will bring socio-economic changes. The results of this study show that Banua Anyar, as a culinary area, offers many restaurants and food stalls serving Banjar specialties. Not only typical of Banjar, but the primary food is also widely available in the Banua Anyar sub-district area. The people living in the Banua Anyar sub-district carry out many economic activities, namely processing and producing goods, distributing goods, and consuming goods traded in the Banua Anyar sub-district.